Experimental Study of the Slit Spacing and Bed Height on the Thermal Performance of Slit-Glazed Solar Air Heater - Mousavi, Seyyed Mahdi Taheri; Egelioglu, Fuat (Hindawi Ltd, 2017)
The thermal performances of three slit-glazed solar air heaters (SGSAHs) were investigated experimentally. Three SGSAHs with different bed heights (7 cm, 5 cm, and 3 cm) were fabricated with multiple glass panes used for glazing. The length, width, and thickness of each pane were 154 cm, 6 cm, and 0.4 cm, respectively. Ambient air was continuously withdrawn through the gaps between the glass panes by fans. The experiments were conducted for four different gap distances between the glass panes (0.5 mm, 1 mm, 2 mm, and 3 mm) and the air mass flow rate was varied between 0.014 kg/s and 0.057 kg/s. The effects of air mass flux on the outlet temperature and thermal efficiency were studied. For the SGSAH with bed height of 7 cm and glass pane gap distance of 0.5 mm, the highest efficiency was obtained as 82% at a mass flow rate of 0.057 kg/s and the air temperature difference between the inlet and the outlet (Delta T) was maximum (27 degrees C) when the mass flow rate was least. The results demonstrate that for lower mass flow rates and larger gaps, the performance of SGSAH with a bed height of 3 cm was better compared to that of others. However, for higher mass flow rates, the SGSAH with 7 cm bed height performed better.
Keywords: Thermohydraulic Performance; Flow Distribution; Wire Mesh; Collector; Fins; Efficiency; Design; Single; Energy